VARIASI LATIHAN SHADOW MENINGKATKAN PUKULAN FOREHAND - Husni Fahritsani; Sugar Wanto; I Made Andika Bayu; Mutiara Fajar; Ardo Okilanda (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The purpose of this research is to improve basic forehand drive technique skills. The research method used is sports action research method. The research procedures used are planning, implementation, observation, reflection. The subjects of this study were 31 semester 5 physical education students at PGRI Palembang University. This study applies the resulting method, namely in the form of variations with shadow exercises, the basic technical skills of forehand drive strokes in the game of tennis are increased. The results of the achievement score reached 82.65% where the result is the average score of students where students are the subjects of this study.In a good position, the shadow movement determines how a player anticipates the direction of a fast punch from the opponent, the shadow movement also looks at the opponent's direction so that the forehand returns according to the opponent's difficult places.